The political satire of Mojok.co in the 2019 Indonesian election - Sunarso Sunarso; Benni Setiawan; Ni Putu Pande Satya Anjani (Heliyon, 2022)
This article aims to discuss Mojok.co’s style of political satire as an alternative to political discussion. Mojok.co packages political messages that are easy to understand. This article presents Mojok.co’s sophisticated style in packaging political messages in a “naughty” style but evokes political awareness. This study employs a qualitative content analysis which enables to collect data in the form of words, meanings, symbols, ideas, themes and other forms of communication messages. Qualitative content analysis allows the communication media content to be recorded and further analyzed. The content analyzed in this study is political content on Mojok.co’s Instagram account related to the 2019 election. The results of this study show that the content on Mojok.co demonstrates satire, joking, and ridicule discussion on politics. Moreover, Mojok.co’s satire content functions as supporting elements of the image display so that the audience can easily understand the messages. Mojok.co’s infographic content design combines the elements of colour, illustration, and typography to represent the signs. Mojok.co’s satirical style also offers joyful political discussions. The meaning of politics can be interpreted in a simple, light, and entertaining discussion. Therefore, political satire can be an alternative style of discussion.